The use of accelerometers to quantify external load in rugby league match play - Turner, J. A.; Delves, R.; Compton, H. R.; Penfold, L.; Duthie, G. M. (Frontiers in Sports and Active Living, 2025)
Introduction: This study quantified the distribution of accelerometer data in rugby league competition.